Influence of metal ions Pb, Zn, As, Sb and Ag in the natural activation of sphalerite during flotation of lead-silver - Azañero Ortiz, Ángel (2013)
The subject study deals on the effects which Pb, Zn, As, Sb and Ag ions may exert on accelerating chemical reaction of sphalerite on lead flotation. If this action occurs lead concentrate is contaminated and also it decreases the zinc recovery of the zinc circuit.Three different ore samples at various degrees of zinc activation were used to analyze this problem. Results show that further investigation is required to find out whether or not the activation of zinc is due to the contained As ions or due to soluble metal salts of Pb, Zn, Sb and Ag.